Examining the impact of medical legal partnerships in improving outcomes on the HIV care continuum: rationale, design and methods - Miguel Muñoz-Laboy; Omar Martinez; Robin Davison; Isa Fernandez (BMC, 2019)
Abstract Background Over the past two decades, we have seen a nationwide increase in the use of medical-legal partnerships (MLPs) to address health disparities affecting vulnerable populations. These partnerships increase medical teams' capacity to address social and environmental threats to patients' health, such as unsafe housing conditions, through partnership with legal professionals. Despite expansions in the use of MLP care models in health care settings, the health outcomes efficacy of MLPs has yet to be examined, particularly for complex chronic conditions such as HIV. Methods This on-going mixed-methods study utilizes institutional case study and intervention mapping methodologies to develop an HIV-specific medical legal partnership logic model. Up-to-date, the organizational qualitative data has been collected. The next steps of this study consists of: (1) recruitment of 100 MLP providers through a national survey of clinics, community-based organizations, and hospitals; (2) in-depth interviewing of 50 dyads of MLP service providers and clients living with HIV to gauge the potential large-scale impact of legal partnerships on addressing the unmet needs of this population; and, (3) the development of an MLP intervention model to improve HIV care continuum outcomes using intervention mapping. Discussion The proposed study is highly significant because it targets a vulnerable population, PLWHA, and consists of formative and developmental work to investigate the impact of MLPs on health, legal, and psychosocial outcomes within this population. MLPs offer an integrated approach to healthcare delivery that seems promising for meeting the needs of PLWHA, but has yet to be rigorously assessed within this population.